The Neuropeptide Allatostatin A Regulates Metabolism and Feeding Decisions in Drosophila. - Hentze, J.L.; Carlsson, M.A.; Kondo, S.; Nässel, D.R.; Rewitz, K.F. (Scientific reports, 2015)
Coordinating metabolism and feeding is important to avoid obesity and metabolic diseases, yet the underlying mechanisms, balancing nutrient intake and metabolic expenditure, are poorly understood. Several mechanisms controlling these processes are conserved in Drosophila, where homeostasis and energy mobilization are regulated by the glucagon-related adipokinetic hormone (AKH) and the Drosophila insulin-like peptides (DILPs). Here, we provide evidence that the Drosophila neuropeptide Allatostatin A (AstA) regulates AKH and DILP signaling. The AstA receptor gene, Dar-2, is expressed in both the insulin and AKH producing cells. Silencing of Dar-2 in these cells results in changes in gene expression and physiology associated with reduced DILP and AKH signaling and animals lacking AstA accumulate high lipid levels. This suggests that AstA is regulating the balance between DILP and AKH, believed to be important for the maintenance of nutrient homeostasis in response to changing ratios of dietary sugar and protein. Furthermore, AstA and Dar-2 are regulated differentially by dietary carbohydrates and protein and AstA-neuronal activity modulates feeding choices between these types of nutrients. Our results suggest that AstA is involved in assigning value to these nutrients to coordinate metabolic and feeding decisions, responses that are important to balance food intake according to metabolic needs.